The Development of a Nurse-Led Internet-Based Learning and Self-care Program for Cancer Patients With Symptoms of Anxiety and Depression—A Part of U-CARE. Issue 5 (September 2017) - Hauffman, Anna; Alfonsson, Sven; Mattsson, Susanne; Forslund, Marina; Bill-Axelson, Anna; Nygren, Peter; Johansson, Birgitta
Abstract : Background: Having access to information about the disease and being encouraged to participate in self-care activities may reduce anxiety and depression symptoms in cancer patients. Internet-based interventions may be one way to support effective self-care strategies to improve emotional well-being and health-related quality of life. Objective: The aim of this study was to describe the development and acceptance of an Internet-based program intended to support cancer patients with anxiety and depression symptoms. Methods: A structured collaboration between patients, clinicians, and researchers was used to develop a theory- and evidence-based interactive health communication application (IHCA) based on Orem's self-care deficit nursing theory with influences from Bandura's social learning theory and psychoeducation. Results: The result is an IHCA described as a Nurse-led, Internet-based Learning and Self-care program that helps patients to perform self-care using different types of material in interaction with patients and healthcare staff. The acceptance of the program is consistent with the results of similar studies. Conclusions: Collaboration between patients, clinicians, and researchers seems to be a fruitful approach in the development of an IHCA aiming to support cancer patients' self-care strategies. Well-designed intervention studies are needed to evaluate the effects of the IHCA. Implications for Practice: This article suggests a theoretical foundation for an IHCA and allows researchers and healthcare providers to take part in the discussion regarding format and content of IHCAs.